Impact of Capitalization on Financial Performance of Jaiz Bank plc - Shehu, Farida Mohammed; Sani, Kasim Muhammad (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This paper investigated the impact of capitalisation on the financial performance of Jaiz Bank Plc, the first full-fledged Islamic bank in Nigeria. Using quantitative research methodology, the study examined the relationship between risk management and financial performance, such as Return on Assets (ROA). The data were obtained from the published financial statements of the Jaiz Bank Plc in Nigeria from 2013 to 2023. The study employed the multiple regression technique. The SPSS software package version 26 was used to carry out the analysis. Descriptive statistics and regression analysis are employed to analyse the data. The findings showed that capitalisation (CAP) significantly impacts ROA. It is, therefore, recommended that Jaiz Bank Plc should improve capitalisation strategies to enhance ROA. This can be achieved by efficiently allocating its capital to high-yield Sharia-compliant investments and enhancing capitalisation through equity financing or issuing Sukuk.